Flexible Thermoelectric Double‐Layer Inorganic/Organic Composites Synthesized by Additive Manufacturing. (16th July 2020) - Du, Yong; Chen, Jiageng; Meng, Qiufeng; Xu, Jiayue; Lu, Jun; Paul, Biplab; Eklund, Per
Abstract: This study shows an approach to combine a high electrical conductivity of one composite layer with a high Seebeck coefficient of another composite layer in a double‐layer composite, resulting in high thermoelectric power factor. Flexible double‐layer‐composites, made from Bi2 Te3 ‐based‐alloy/polylactic acid (BTBA/PLA) composites and Ag/PLA composites, are synthesized by solution additive manufacturing. With the increase in Ag volume‐ratio from 26.3% to 41.7% in Ag/PLA layers, the conductivity of the double‐layer composites increases from 12 S cm −1 to 1170 S cm −1, while the Seebeck coefficient remains ≈80 μV K −1 at 300 K. With further increase in volume ratio of Ag until 45.6% in Ag/PLA composite layer, the electrical conductivity of the double‐layer composites increases to 1710 S cm −1, however, with a slight decrease of the Seebeck coefficient to 64 μV K −1 . The electrical conductivity and Seebeck coefficient vary only to a limited extent with the temperature. The high Seebeck coefficient is due to scattering of low energy charge carriers across compositionally graded interfaces. A power factor of 875 μW m −1 K −2 is achieved at 360 K for 41.7 vol.% Ag in the Ag/PLA layers. Solution additive manufacturing can directly print this double‐layer composite into intricate geometries, making this process is promising for large‐scale fabrication of thermoelectric composites. Abstract : A flexible double‐layer composite with high thermoelectric power factor is demonstrated, combining the high electrical conductivity of one composite layer with a high Seebeck coefficient of another composite layer. Solution additive manufacturing can directly print this double‐layer composite into intricate geometries and is promising for large‐scale fabrication of thermoelectric composites and devices.